Changes in Anti-Group A Rotavirus Antibody Seroprevalence and Levels in the Western Gyeongnam Province of Korea Over 16 Years - Seo, Ji-Hyun; Park, Jung Je; Lim, Jae-Young; Jun, Jin-Su; Park, Chan-Hoo; Woo, Hyang-Ok; Youn, Hee-Shang; Kwon, Young-Cheol; Kang, Hyung-Lyun; Baik, Seung-Chul; Lee, Woo-Kon; Cho, Myung-Je; et al. (Journal of Korean medical science, 2013)
To observe how anti-group A rotavirus antibody seropositivity rates and levels have changed in the western region of Gyeongnam Province, 2,030 serum samples collected at four collection periods (1989-1990, 1994-1995, 1999-2000, and 2004-2005) were tested by Enzyme-Linked Immunosorbent Assay for IgG, and IgA antibodies reacting to recombinant VP6 protein. The seroprevalences exhibit no regular patterns over a 16-yr period. For all four collection periods, the anti-rVP6 IgG levels rose steadily during the first 5 months of life, after which they remained high. However, the 2-9 yr and 10-39 yr groups had significantly higher IgG levels in 1999-2000 and 2004-2005, respectively, than in the other collection periods. The 1-5 mo, 40- ≥ 60 yr, and 4-29 yr groups had significantly higher IgA levels in 1989-1990, 1999-2000, and 2004-2005, respectively. The 4 yr (25.0%), 5-9 yr (18.8%), 10-14 yr (41.1%), 20-29 yr (35.0%), and 30-39 yr (20.0%) groups in 2004-2005 had significant higher IgA seropositivity rate compared to the other three collection periods. These observations suggest that in the western region of Gyeongnam Province since the late 1990s, rotavirus reinfection has occurred more frequently than previously, with all ages being at risk.